SMART LEARNING MODELS OF CERTIFIED LEGAL TRANSLATORS AND INTERPRETERS - XU, Ming (Comparative Legilinguistics, 2019)
Legal translation has played an important part in the contact between different people and countries in the history, and is playing an even more significant role in the increasingly globalized world nowadays. The paper is to explore smart learning models of legal translation competence that the proper legal translators and interpreters are supposed to grasp. The results find that the prerequisites about knowledge of comparative laws, legal languages and forensic linguistics are the external framework; the legal translational language competence, legal translational knowledge structures, legal translational strategic competence and context of situation are the internal model. Based on the external framework and internal model, exploring translation competence mainly concerns on the organizational competence and pragmatic competence.